Factors associated with self-reported failure of binding release among ACL injured male and female recreational skiers: a catalyst to change ISO binding standards? - Ruedl, G.; Helle, K.; Tecklenburg, K.; Schranz, A.; Fink, C.; Burtscher, M. (British Journal of Sports Medicine, 2016)
Background: Female recreational skiers have twice the rate of knee injuries and three time the rate of ACL injuries compared with their male counterparts. Female skiers suffering from a knee injury reported a significantly higher proportion of failure of binding release than knee injured male skiers.Purpose To evaluate factors associated with failure of binding release among ACL injured male and female recreational skiers.Study design Cohort study. Methods: Among a cohort of 498 recreational skiers (68% females) suffering from an ACL injury (complete rupture or partial rupture), age, sex, height, weight, self-reported skill level and self-reported risk taking behaviour, gear origin, ski length, date of last binding adjustment, perceived speed at the moment of injury, type of fall, and failure of binding release of the ski of the injured knee, were collected by questionnaire. Results: Failure of binding release was reported within 78% of cases and was significantly higher for females compared to males (83 vs 66%, p<0.001) with an adjusted OR of 2.7 (95% CI 1.7 to 4.4). A higher perceived speed at the moment of injury was significantly associated with a decreasing proportion of failure of binding release. A slow perceived speed was independently associated with failure of binding release (adjusted OR 2.0; 95% CI 1.2 to 3.5). There was a significantly higher proportion of failure of binding release during backward falling compared to forward falling (87 vs 72%, p=0.002); similarly, a higher proportion of failure of binding release occurred in cases of complete rupture compared with a partial tear of the ACL (81 vs 64%, p=0.001), respectively. Conclusions: Among this cohort of ACL-injured skiers, failure of binding release was significantly associated with female sex, a slow perceived speed at the moment of injury and complete rupture of the ACL.